1994
DOI: 10.1007/bf02090067
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole ameliorates aspirin-induced gastroduodenal injury

Abstract: Aspirin and nonsteroidal antiinflammatory drugs (NSAIDs) damage the gastroduodenal epithelium by two mechanisms: direct toxic effects and effects related to the depletion of endogenous prostaglandins. The prostaglandin-depleted mucosa has increased susceptibility to luminal aggressive factors, yet the role of acid in the pathogenesis of the NSAID ulcer is controversial. In humans, standard doses of H2-receptor antagonists prevent only duodenal injury and provide no protection for the gastric mucosa. It is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 26 publications
2
24
0
2
Order By: Relevance
“…At least 2 randomized, controlled trials have demonstrated that mucosal gastric injury from aspirin at similar or higher doses than those used in our study can be abolished by adjuvant use of the proton pump inhibitor omeprazole. 40,41 We therefore take the position that the gastrointestinal bleeding risk of high-dose aspirin is acceptable, provided that a proton pump inhibitor is additionally prescribed. This was supported by the fact that no serious gastric or bleeding events requiring medical attention were observed in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…At least 2 randomized, controlled trials have demonstrated that mucosal gastric injury from aspirin at similar or higher doses than those used in our study can be abolished by adjuvant use of the proton pump inhibitor omeprazole. 40,41 We therefore take the position that the gastrointestinal bleeding risk of high-dose aspirin is acceptable, provided that a proton pump inhibitor is additionally prescribed. This was supported by the fact that no serious gastric or bleeding events requiring medical attention were observed in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…Omeprazole significantly decreased aspirin-induced gastric mucosal injury (p Ͻ 0.01) by protecting 85% of the subjects from extensive erosions or ulcer, whereas 70% of the subjects developed severe injury (rate 3 or 4 on 0 -4 scale) on aspirin and placebo. No duodenal injury was seen in any grade or any subject on omeprazole, whereas 50% on placebo developed erosions and 15% had DU (p Ͻ 0.001) (65).…”
Section: Proton Pump Inhibitorsmentioning
confidence: 94%
“…These results extend the results of other, smaller and/or non-controlled studies of primary prevention by PPIs of short-term non-selective NSAID-related GI side effects [31]. Most such studies have utilized aspirin (ASA) [32][33][34][35][36][37][38][39]. The available evidence suggests that OMP results in an approximately 75% decrease in the incidence of endoscopic lesions related to either low-dose or antiinflammatory dose of ASA daily [32,37].…”
Section: Discussionmentioning
confidence: 51%
“…Most such studies have utilized aspirin (ASA) [32][33][34][35][36][37][38][39]. The available evidence suggests that OMP results in an approximately 75% decrease in the incidence of endoscopic lesions related to either low-dose or antiinflammatory dose of ASA daily [32,37]. In one short-term study of primary prevention of NPX-related injury, OMP 40 mg daily, begun 48 h before starting NPX, resulted in approximately 40% reduction of gastric injury in 15 young, healthy volunteers [35].…”
Section: Discussionmentioning
confidence: 99%